Sodium bicarbonate supplementation delays neuromuscular fatigue without changes in performance outcomes during a basketball match simulation protocol - Ansdell, P.; Dekerle, J. (The Journal of Strength and Conditioning Research, 2020)
To investigate the development of neuromuscular fatigue during a basketball game simulation and to ascertain whether sodium bicarbonate (NaHCO3) supplementation attenuates any neuromuscular fatigue that persists. Ten participants ingested 0.2 g·kg-1 of NaHCO3 (or an equimolar placebo dosage of sodium chloride [NaCl]) 90 and 60 minutes before commencing a basketball game simulation (ALK-T vs. PLA-T). Maximal voluntary isometric contractions (MVICs) of the knee extensors and potentiated high- (100 Hz) and low- (10 Hz) frequency doublet twitches were recorded before and after each match quarter for both trials. In addition, 15-m sprint times and layup completion (%) were recorded during each quarter. Maximal voluntary isometric contraction, 100- and 10-Hz twitch forces declined progressively in both trials (p = 0.05) with a less pronounced decrease in MVIC during ALK-T (p < 0.01). Both 100- and 10-Hz twitch forces were also significantly greater in ALK-T (p = 0.05). Fifteen-meter sprint time increased over the course of both trials (~2%, p < 0.01); however, no significant condition or time effect was found for layup completion (p > 0.05). A basketball simulation protocol induces a substantial amount of neuromuscular (reduction in knee extensor MVICs) and peripheral fatigue with a concomitant increase in 15-m sprint time over the protocol. NaHCO3 supplementation attenuated the rate of fatigue development by protecting contractile elements of the muscle fibers. This study provides coaches with information about the magnitude of fatigue induced by a simulated basketball game and provides evidence of the efficacy of NaHCO3 in attenuating fatigue.